Pemanfaatan Teknologi Informasi Untuk Meningkatkan Kemampuan Perencanaan dan Kematangan Karir Siswa - Sodiq, Darojaturroofi'ah; Herdi, Herdi (Jurnal Paedagogy, 2021)
This study aims to analyze the use of information technology in planning and career maturity of students. This study uses a systematic literature review approach. The journals used in this systematic literature review were obtained through a database of national and international journal providers through Google Scholar which were then analyzed systematically. The results of this study indicate that the use of information technology can improve planning and career maturity in students. Both the media such as blogs, multimedia and the use of the internet can be adequate resources for student career advancement.